84.3k views
3 votes
(3^3 - 9 )^2 ? How would I simplyify this expression

2 Answers

7 votes

Answer:

The simplest result is 324.

Explanation:

Note that 3^3 = 27. Thus, 9 is a factor of both 3^3 and 9 inside those parentheses.

Then (3^3 - 9 )^2 is the same as [ 9(3-1) ]^2, or

[ 9(2) ]^2, or 81*4 = 324.


User Thinclient
by
5.5k points
6 votes

(3^3 - 9 )^2

First do what is inside the parenthesis:

3^3 = 27

Now you have:

(27-9)^2

Subtract:

27-9 = 18

Now you have:

(18)^2

Raise 18 to the second power:

18^2 = 324

User Effect
by
5.5k points